IMPLEMENTASI NILAI KULTUR DAN KARAKTER BAGI PESERTA DIDIK DI PONDOK PESANTREN - Arif Muzayin Shofwan (Jurnal Studi Pesantren, 2026)
Pesantren as the oldest Islamic religious educational institution in Indonesia is always interesting for researchers to study and research. This study discusses the implementation of cultural and character values ​​for students in Islamic boarding schools. The data analysis technique uses content analysis by sorting things that are in accordance with the focus and objectives of the study. This study found that there are 17 cultural and character values ​​of Islamic boarding schools, namely: deepening religious knowledge, dormitory, obedience, exemplary, piety, independence, discipline, simplicity, tolerance, accepting what is, humility, fortitude, solidarity, sincerity, steadfastness, community, and cleanliness. The seventeen cultures and characters of Islamic boarding schools are significant to the content of the Qur'an and Hadith. For example, deepening religious knowledge is significant to Surah Al-Taubah verse 122, Surah Al-Mujadalah verse 11, HR. Ibnu Majah, HR. Thabrani, HR. Muslim, HR. Turmudzi, HR. Bukhari, and HR. Abu Daud. Compliance is significant with Surah An-Nisa verse 59, HR. Muslim. Exemplary behavior is significant with Surah Al-Ahzab verse 21, and Surah Al-Qalam verse 4. Piety is significant in Surah Al-Baqarah verse 21, Surah Al-Mu’min verse 60, and HR. Turmudzi, HR. Hakim, HR. Ahmad, and others. Independence is significant with Surah Al-Mudasir verse 38, HR. Muslim, Abu Daud, and HR. Bukhari. Discipline is significant with Surah Al-Jumuah verse 9-10, HR. Bukhari, HR. Hakim, and others.